Polityka rządu José Marii Aznara Lópeza wobec Kuby (1996-2004) - Domejko-Kozera, Patrycja (Acta Universitatis Lodziensis. Folia Historica, 2008)
After the victory of People’s Party (Partido Popular) in the election on 3 March 1996 the government of José Maria Aznar with the foresight of protection of human rights and democratization adopted a strict policy towards Cuba, the country linked with Spain by numerous bonds: historical, linguistic, cultural, economic ones, not to mention relations of soieties. This change was the result of the strategy formulated by the PP government of alliance with the USA whose relations with Castro regime had been hostile for years. The stages in the Spanish-Cuban relations in the years 1996-2004 coincided with periods in Washington-Havana relations. The following stages can be distinguished in this period: gradual deterioration of bilateral relations leading to diplomatic crisis (May 1996—April 1998), normalization (from April 1998) and renewed crisis (with the climax after adoption by the European Union sanctions on Cuba in June 2003). The PP government actions concerned mostly political and diplomatic spheres, both on bilateral (Spain did not appoint an ambassador in Havana for 1,5 ywar) and communitarian lovel (European Union Common Position of 2 December 1996 on Cuba, UE sanctions on Cuba). The government actions did not affect the economic sphere. Despite the fact that tension in Madrid-Havana contacts had negative effect on economy, during the years of Aznar’s government Spanish trade with Cuba flourished. Having adopted a tough policy towards Cuba, the PP government criticized US embargo on Cuba and Hclms-Burton Act. The policy of the government of PP towards Cuba was criticized by the opposition. It did not contribute to the improvement of human rights and democratic rules on the island, but it strengthened Spanish-American relations.